The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1177/0193945918785349c
|View full text |Cite
|
Sign up to set email alerts
|

A Quality Improvement Project to Improve Provision of Asthma Action Plans

Abstract: associated with PA performance in the expected direction. The findings underscore the importance of developing PA interventions for pregnant women that are guided by a theoretical framework, taking into consideration nonmodifiable determinants of PA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…There was also a poor attitude reported in the patients' respondents in which majority felt that they were for very sick patients; Majority of the patients indicated that the use of PAAPs should be used for the very sick people. The practice was poor even for those few who had these tools; in which from a sample of 52 patients who were found to have a PAAPs card those who used to check for their card at home while low count among the respondents who didn't check their card [21][22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…There was also a poor attitude reported in the patients' respondents in which majority felt that they were for very sick patients; Majority of the patients indicated that the use of PAAPs should be used for the very sick people. The practice was poor even for those few who had these tools; in which from a sample of 52 patients who were found to have a PAAPs card those who used to check for their card at home while low count among the respondents who didn't check their card [21][22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%